Is there passion for public service in authoritarian bureaucracies? Exploring public service motivation across regime types. Issue 1 (2nd January 2023) - Ripoll, Guillem; Rode, Martin
ABSTRACT: Although previous research has explored broadly the determinants of public service motivation (PSM), little is known about how it is affected by formal institutional variations. This article examines the presence of PSM in the bureaucracies of democratic and autocratic political regimes. Merging data from the four waves of the International Social Survey Programme with a recent classification of regime types, this study confirms that autocracies seem neither to diminish public servants' levels of PSM, nor hinder its cultivation. In fact, we find indications that PSM is likely to be higher in autocracies, where the positive effect of relatedness on PSM is also stronger than in democracies, albeit the latter is partially non-significant. Future research and practical implications of the findings are further discussed.